Check your Trigonometric Application

Geometry Level 3

If 5 tan ( α ) tan ( β ) = 3 5 \tan(\alpha)\tan(\beta)=3 , then find the value of cos ( α + β ) cos ( α β ) \dfrac{\cos\left(\alpha+\beta\right)}{\cos\left(\alpha-\beta\right)}


Try more Trigonometry Problems .


The answer is 0.25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Discussions for this problem are now closed

Sandeep Bhardwaj
Dec 2, 2014

Given : 5. t a n α . t a n β = 3 5.tan\alpha.tan\beta=3

5. s i n α . s i n β c o s α . c o s β = 3 \implies \dfrac{5.sin\alpha.sin\beta}{cos\alpha.cos\beta}=3

s i n α . s i n β c o s α . c o s β = 3 5 \implies \dfrac{sin\alpha.sin\beta}{cos\alpha.cos\beta}=\dfrac{3}{5}

Using componendo and dividendo,

c o s α . c o s β + s i n α . s i n β c o s α . c o s β s i n α . s i n β = 5 + 3 5 3 = 2 \dfrac{cos\alpha.cos\beta+sin\alpha.sin\beta}{cos\alpha.cos\beta-sin\alpha.sin\beta}=\dfrac{5+3}{5-3}=2

c o s ( α β ) c o s ( α + β ) = 4 \implies \dfrac{cos\left(\alpha-\beta\right)}{cos\left(\alpha+\beta\right)}=4

T h e r e f o r e , c o s ( α + β ) c o s ( α β ) = 1 4 = 0.25 Therefore, \quad \dfrac{cos\left(\alpha+\beta\right)}{cos\left(\alpha-\beta\right)}=\dfrac{1}{4}=\boxed{0.25}

What does Compendo and Divendo mean? Could someone please explain?

Ritu Roy - 6 years, 6 months ago

Componendo and Dividendo means : If a b = c d \dfrac{a}{b}=\dfrac{c}{d} , then we can say that a + b a b = c + d c d \dfrac{a+b}{a-b}=\dfrac{c+d}{c-d} .That means that we can apply the + , +,- operators on both the sides with Numerators and Denominators. @Ritu Roy

Sandeep Bhardwaj - 6 years, 6 months ago

Here is a note that I wrote up in the past about how to use it.

Calvin Lin Staff - 6 years, 6 months ago

I went the other way round . I divided the numerator and denominator in cos(a-b)/cos(a+b) by cos(a)cos(b) and then substituted the value of tan(a)tan(b).

Keshav Tiwari - 6 years, 6 months ago

exactly the same!

Asim Das - 6 years, 5 months ago

My solution involves the Product-to-Sum formulas:

sin ( u ) sin ( v ) = 1 2 [ cos ( u v ) cos ( u + v ) ] \sin { \left( u \right) } \sin { \left( v \right) } =\frac { 1 }{ 2 } \left[ \cos { \left( u-v \right) } -\cos { \left( u+v \right) } \right]

cos ( u ) cos ( v ) = 1 2 [ cos ( u v ) + cos ( u + v ) ] \cos { \left( u \right) } \cos { \left( v \right) } =\frac { 1 }{ 2 } \left[ \cos { \left( u-v \right) } +\cos { \left( u+v \right) } \right]

Given: 5 tan ( α ) tan ( β ) = 3 5\tan { \left( \alpha \right) } \tan { \left( \beta \right) } =3

5 sin α sin β cos α cos β = 3 \Longrightarrow \quad 5\frac { \sin { \alpha } \sin { \beta } }{ \cos { \alpha } \cos { \beta } } \quad =\quad 3

5 sin α sin β = 3 cos α cos β \Longrightarrow \quad 5\sin { \alpha } \sin { \beta } \quad =\quad 3\cos { \alpha } \cos { \beta }

Using said formulas, we get

5 × 1 2 [ cos ( α β ) cos ( α + β ) ] = 3 × 1 2 [ cos ( α β ) + cos ( α + β ) ] 5 cos ( α β ) 5 cos ( α + β ) = 3 cos ( α β ) + 3 cos ( α + β ) 2 cos ( α β ) = 8 cos ( α + β ) cos ( α + β ) cos ( α β ) = 2 8 = 0.25 5\quad \times \quad \frac { 1 }{ 2 } \left[ \cos { \left( \alpha -\beta \right) } -\cos { \left( \alpha +\beta \right) } \right] \quad =\quad 3\quad \times \quad \frac { 1 }{ 2 } \left[ \cos { \left( \alpha -\beta \right) } +\cos { \left( \alpha +\beta \right) } \right] \\ \Longrightarrow \quad 5\cos { \left( \alpha -\beta \right) } \quad -\quad 5\cos { \left( \alpha +\beta \right) } \quad =\quad 3\cos { \left( \alpha -\beta \right) } \quad +\quad 3\cos { \left( \alpha +\beta \right) } \\ \Longrightarrow \quad 2\cos { \left( \alpha -\beta \right) } \quad =\quad 8\cos { \left( \alpha +\beta \right) } \\ \Longrightarrow \quad \frac { \cos { \left( \alpha +\beta \right) } }{ \cos { \left( \alpha -\beta \right) } } \quad =\quad \frac { 2 }{ 8 } \quad =\quad \boxed { 0.25 }

Akhil Kumar
Dec 6, 2014

cos(a+b)/cos(a-b) = (cosa.cosb-sina.sinb)/(cosa.cosb+sina.sinb) Now dividing numerator and denominator by sina.sinb,we get (cota.cotb-1)/(cota.cotb+1) now putting cota.cotb=5/3 (Given) we get, (5/3-1)/(5/3-1)=1/4=0.25

Well I solved it with some different way, I am considering alpha as A and beta as B as tanAtanB=3/5 ------- let Eq No 1, now opening cos(A+B)/cos(A-B)=cosAcosB-SinAsinB/cosAcosB+sinAsinB dividing numerator and denominator by cosAcosB. =1-tanAtanB/1+tanAtanB =1-3/5 / 1 + 3/5 =2/8=0.25

Perfect . .......,.............

Wael Noaman - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...